12 Monkeys - Kord, Susanne (Constellations., 2019)
This volume examines Terry Gilliam's 12 Monkeys (1995) with an eye to the film's major themes, including mental illness, conspiracy theories, the impossibility of human closeness, and the nature of reality. It reads 12 Monkeys's portrayal of time travel in light of Einstein's ideas about time and the problem of free will versus determinism.